2017
DOI: 10.1161/strokeaha.117.017128
|View full text |Cite
|
Sign up to set email alerts
|

Circulating FABP4 (Fatty Acid–Binding Protein 4) Is a Novel Prognostic Biomarker in Patients With Acute Ischemic Stroke

Abstract: Data show that FABP4 is a novel independent prognostic marker improving the currently used risk stratification of stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 35 publications
1
40
0
Order By: Relevance
“…The lipid binding protein family consists of small (~15 kDa) soluble proteins that serve as modulators of intracellular lipid homeostasis by regulating long chain fatty acid transport in the nuclear and extra-nuclear cell compartments. The FABP4 isoform is predominantly expressed in adipose tissue, but also circulates in human plasma [73,74]. It is involved in intracellular lipid trafficking and has a role in the development of insulin resistance, atherosclerosis, and inflammatory processes.…”
Section: Alterations In Fatty Acids Metabolismmentioning
confidence: 99%
“…The lipid binding protein family consists of small (~15 kDa) soluble proteins that serve as modulators of intracellular lipid homeostasis by regulating long chain fatty acid transport in the nuclear and extra-nuclear cell compartments. The FABP4 isoform is predominantly expressed in adipose tissue, but also circulates in human plasma [73,74]. It is involved in intracellular lipid trafficking and has a role in the development of insulin resistance, atherosclerosis, and inflammatory processes.…”
Section: Alterations In Fatty Acids Metabolismmentioning
confidence: 99%
“…Functional outcome was assessed by the modified Rankin Scale (mRS) [16] blinded to serum biomarkers. A good functional outcome was defined as an mRS of 0-2 points, whereas a poor outcome was defined as an mRS of > 2 points [17]. Secondary end points were all-cause mortality within 6 months.…”
Section: Clinical Variables and Follow-upmentioning
confidence: 99%
“…The prognostic value of FABP4 in cardiovascular and cerebrovascular diseases was previously reported. Tu et al [24] showed that FABP4 was a novel independent prognostic marker in patients with ischemic stroke. FABP4 was also related to atherogenesis and poor outcome in acute ischemic stroke patients with carotid atherosclerosis [25].…”
Section: Discussionmentioning
confidence: 99%